2021
DOI: 10.3389/fmars.2020.599984
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Relationships Within Chrysogorgia (Alcyonacea: Octocorallia), a Morphologically Diverse Genus of Octocoral, Revealed Using a Target Enrichment Approach

Abstract: The octocoral genus Chrysogorgia (Duchassaing and Michelotti, 1864) contains 81 nominal species that are ecologically important components of benthic communities. Taxonomic examination of a large set of samples revealed many provisional new species, exhibiting a wide range of morphological variation. We established nine, distinct morphological groups of Chrysogorgia s.l. that were hypothesized to represent distinct genera. Here, we applied a recently developed universal target enrichment bait method for octoco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 60 publications
0
20
0
Order By: Relevance
“…Individuals in the genus Chrysogorgia s.l. were assigned, on the basis of morphological characteristics, by coauthor CBU to the established groups of Untiedt et al [18] to better quantify the observed diversity within the genus while it is undergoing a major redescription. We were conservative in our identifications, and only identified individuals to genus and/or species when we were confident that characteristics matched the relevant taxonomic literature [62][63][64][65][66][67][68][69][70].…”
Section: Taxon Identification and Nomenclature Used Throughout This S...mentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals in the genus Chrysogorgia s.l. were assigned, on the basis of morphological characteristics, by coauthor CBU to the established groups of Untiedt et al [18] to better quantify the observed diversity within the genus while it is undergoing a major redescription. We were conservative in our identifications, and only identified individuals to genus and/or species when we were confident that characteristics matched the relevant taxonomic literature [62][63][64][65][66][67][68][69][70].…”
Section: Taxon Identification and Nomenclature Used Throughout This S...mentioning
confidence: 99%
“…The genus Chrysogorgia is another taxonomically confusing group of octocorals. While it is one of the most abundant and diverse groups of octocorals, with 71 currently accepted species [17], recent investigations into the phylogenetic relationships among species within this genus have led to the proposal of 11 candidate genera [18], each of which has been assigned a group number in advance of formal description. There are fewer taxonomic problems within Primnoidae due to the work of dedicated museum taxonomists, unburdened by academic duties that university-based taxonomists face, and perhaps due to the frequent incorporation of genetics into their systematics, which helps test and reinforce the usefulness of certain taxonomic characters (e.g., [19][20][21]).…”
Section: Introductionmentioning
confidence: 99%
“…A preliminary morphological examination of sclerites from Swiftia exserta phenotypes was conducted using scanning electron microscopy and the results suggested no significant difference in sclerite morphology and composition, spindle size (ANOVA p = 0.97), or capstan size (ANOVA p = 0.61) between the two morphotypes [13,20]. Thus, we proceed with the hypothesis that the impacted species of Swiftia with white polyps in the GoMx is in fact a conspecific of S. exserta, exhibiting phenotypic plasticity, a phenomenon that is very common among octocorals [28,35,[56][57][58]. The red-polyp variant of S. exserta has only been observed at shallower depths (~10-30 m), while the white-polyp variant occurs at mesophotic depths from 50-200 m, and they share a haplotype of mtMutS.…”
Section: Discussionmentioning
confidence: 98%
“…Our understanding of genetic species boundaries in octocorals is advancing rapidly, particularly through recent research on restriction site associated DNA (RAD) sequencing (Pante et al 2015a;Herrera and Shank 2016;Quattrini et al 2019) and ultraconserved elements (UCEs) (Quattrini et al 2018;Erickson et al 2020;Untiedt et al 2021). However, these methods are not yet universally employed.…”
Section: Octocoral Taxonomy and Current Issuesmentioning
confidence: 99%
“…Perhaps and SNPs by Moore et al 2016). Currently, RAD-sequencing (Pante et al 2015a;Herrera and Shank 2016;Quattrini et al 2019), as well as target-capture enrichment of UCEs and exons (Erickson et al 2020;Quattrini et al 2018Quattrini et al , 2020Untiedt et al 2021) shows promising resolution at all taxonomic levels. Despite the conceptual formalisation of integrative taxonomy in the taxonomic literature over 15 years ago, methodological improvements continue to be necessary, and it is because of this that two of the most enduring problems in octocoral taxonomy have not yet been solved: incongruence between morphological and molecular data, and the nebulous role of interspecific morphological variation in obscuring species boundaries.…”
Section: The Integrative Approach and Lingering Problems In Octocoral Taxonomymentioning
confidence: 99%